Implied Volatility Duration: A measure for the timing of uncertainty resolution - Christian Schlag; Julian Thimme; Rüdiger Weber (Leibniz Institute for Financial Research SAFE, 2020)
We introduce Implied Volatility Duration (IVD) as a new measure for the timing of uncertainty resolution, with a high IVD corresponding to late resolution. Portfolio sorts on a large cross-section of stocks indicate that investors demand on average more than five percent return per year as a compensation for a late resolution of uncertainty. In a general equilibrium model, we show that 'late' stocks can only have higher expected returns than 'early' stocks, if the investor exhibits a preference for early resolution of uncertainty. Our empirical analysis thus provides a purely market-based assessment of the timing preferences of the marginal investor.
urn:nbn:de:hebis:30:3-528964
Keywords: G12; E44; D81; 330; preference for early resolution of uncertainty; implied volatility; cross-sectionof expected stock returns; asset pricing